Red sparrow - Matthews, Jason (New York : Pocket Books, 2018)
Drafted against her will to serve the regime of Vladimir Putin as an intelligence seductress, Dominika Egorova engages in a charged effort of deception and tradecraft with first-tour CIA officer Nathaniel Nash before a forbidden attraction threatens their careers.
Includes excerpt from: Palace of treason.
Movie tie-in.
Keywords: United States. Central Intelligence Agency -- Fiction; Thrillers (Fiction)